Identification of PCTA, a TGIF antagonist that promotes PML function in TGF-β signalling - Faresse, Nourdine (Nature Publishing Group, 2008)
The TGIF homoeodomain protein functions as an important negative regulator in the TGF-β signalling pathway. The inhibitory function of TGIF is executed in part through its ability to sequester the tumour suppressor cytoplasmic promyelocytic leukaemia (cPML) in the nucleus, thereby preventing the phosphorylation of Smad2 by the activated TGF-β type I receptor. Here, we report on the identification of PCTA (PML competitor for TGIF association), a TGIF antagonist that promotes TGF-β-induced transcriptional and cytostatic responses. We provide evidence that PCTA functions in TGF-β signalling by relieving the suppression of Smad2 phosphorylation by TGIF. Furthermore, we demonstrate that PCTA selectively competes with cPML for TGIF association, resulting in the accumulation of cPML in the cytoplasm, where it associates with SARA and coordinates the access of Smad2 for phosphorylation by the activated TGF-β type I receptor. Thus, our findings on the mode of action of PCTA provide new and important insights into the molecular mechanism underlying the antagonistic interplay between TGIF and cPML in the TGF-β signalling network.